BLOKADE LAUT HITAM DAN KETAHANAN PANGAN AFRIKA UTARA: ANALISIS LITERATUR TERHADAP DINAMIKA IMPOR GANDUM - Arfa Nandita, Nisrina; Zaini, Nella; Gracia Damayanti, Abigail; Hotimah, Oot; Mustikarani, Wini (Jurnal Spasial, 2025)
North Africa relies heavily on wheat imports due to limited domestic production influenced by arid climates, scarce arable land, and rapid population growth. The 2022 Black Sea blockade, which disrupted Ukrainian wheat exports, severely affected global supply chains. More than 20 million tons of wheat were trapped in ports, triggering a surge in international food prices. This situation heightened socioeconomic vulnerability in major importing countries such as Egypt, Libya, Tunisia, Morocco, and Algeria. This study applies a systematic literature review, drawing on scholarly articles, international reports, and official data from FAOStat and UN Comtrade. The analysis focuses on wheat import dependency, the blockade’s impact on food prices and access, and mitigation strategies adopted by governments. Findings reveal that countries with high dependency and limited fiscal capacity, such as Egypt and Libya, are more exposed to food crises compared to Algeria and Tunisia. Mitigation strategies include supplier diversification, strengthening strategic reserves, food subsidies, and investment in agricultural technology. The study recommends enhancing regional cooperation, reforming subsidy policies for better targeting, and boosting domestic production through technological innovation as long-term measures to strengthen food security.